(Invited)3D Monolithic Integration. (10th April 2018) - Brunet, Laurent; Batude, Perrine; Fenouillet-Beranger, Claire; Vinet, Maud
Abstract : 3D Monolithic Integration with ultra-small 3D contact pitch (<100nm) offers new 3D partitioning options at fine granularities. This paper reviews potential applications ranging from computing to sensor interface and gives an update on 3DSI device development.